g-Loewner chains, Bloch functions and extension operators into the family of locally biholomorphic mappings in infinite dimensional spaces - GRAHAM, Ian; HAMADA, Hidetaka; KOHR, †Gabriela; KOHR, Mirela (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
In this paper, we survey recent results obtained by the authors on the preservations of the first elements of (g-) Loewner chains and the Bloch mappings by the Roper-Suffridge type extension operators, the Muir type extension opera- tors and the Pfaltzgraff-Suffridge type extension operators into the mappings on the domains in the complex Banach spaces. Mathematics Subject Classification (2010): 32A18, 32A30, 32K05, 30C45, 30C80, 30D45. Received 20 January 2022; Accepted 27 January 2022.